Investigation and genetic polymorphism analysis of rodents infected with Echinococcus in Ili Prefecture, Xinjiang Uygur Autonomous Region, China - Wang, Bingjie; Zhao, Li; Ban, Wanli; Zhang, Xu; Quan, Chenxi; Teliewuhan, Munila; He, Lixiong; Chen, Zhaoyang; Zhang, Zhuangzhi (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionAlveolar echinococcosis (AE) is a life-threatening disease in humans caused by the larval stage of Echinococcus multilocularis. Domestic animals, dogs, foxes, and small mammals constitute the circular chain of AE. To evaluate the infection, distribution, and genetic polymorphism of AE in the Ili Prefecture (Nilka, Xinyuan and Zhaosu), we conducted this survey.MethodsIn June and July 2018, 267 small mammals were captured using water-infusion and mousetrap methods. Combined pathogenic and molecular biological methods were used to observe the histopathology of Echinococcus carried by rodents, amplify the mitochondrial nad1 gene of the pathogen, and investigate the genotype and haplotype diversity of Echinococcus in rodents in Ili Prefecture.ResultsMorphological identification revealed that these captured small mammals belonged to three species, with Microtus gregalis being the dominant species (183/267). Pathological and molecular biological results confirmed that E. multilocularis was the pathogen of echinococcosis in small mammals, with an infection rate of 15.73% (42/267). Among the three areas sampled, the highest infection rate of rodents was 25.45% (14/55) in Nilka County. However, there was no significant difference in the infection rates between regions (χ2 = 5.119, p > 0.05). Of the three captured rodent species, M. gregalis had the highest infection rate of 17.49% (32/183), but there was no significant difference in infection rates between the rodent species (χ2 = 1.364, p > 0.05). Phylogenetic analyses showed that the nad1 gene sequences obtained in this study clustered in the same clade as isolates from China. These isolates contained 21 haplotypes (Hap_1-21); Hap_2 was the most common haplotype (9/42). Furthermore, haplotype diversity (0.925 ± 0.027) and nucleotide diversity (0.01139 ± 0.00119) were higher in the Ili Prefecture than in other regions, indicating that population differentiation was high. Tajima’s D and Fu’s Fs tests were negative (p > 0.10), indicating that the population had expanded. The low fixation index (Fst) ranged from 0.00000 to 0.16945, indicating that the degree of genetic differentiation was different among different populations.DiscussionIn summary, Ili Prefecture is a high incidence area of AE, and Microtus spp. may play an important role in the transmission of AE in this area. The results of this study provide basic data for further study of the molecular epidemiology, genetic differences, and control of E. multilocularis in the Ili Prefecture, Xinjiang.